2016
DOI: 10.1063/1.4972995
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry, growth kinetics, and epitaxial stabilization of Sn2+ in Sn-doped SrTiO3 using (CH3)6Sn2 tin precursor

Abstract: PbTiO3-based ferroelectrics have impressive electroactive properties, originating from the Pb2+ 6s2 electron lone-pair, which cause large elastic distortion and electric polarization due to cooperative pseudo Jahn-Teller effect. Recently, tin-based perovskite oxide (SnTiO3) containing Sn2+ and a chemistry similar to that of the 6s2 lone-pair has been identified as a thermally stable, environmentally friendly substitute for PbTiO3-based ferroelectrics. However experimental attempts to stabilize Sn2+ on the A-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
1
8
0
3
Order By: Relevance
“…Despite its simple structure and unique properties, the quality of SnO films reported in the literature varies greatly [15,[21][22][23][24][25][26][27]. Part of the challenge with obtaining high-quality SnO is stabilizing Sn 2+ over Sn 4+ [28,29]. Indeed, thermodynamic phase diagrams omit SnO considering it metastable and to disproportionate to Sn and SnO 2 [30].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its simple structure and unique properties, the quality of SnO films reported in the literature varies greatly [15,[21][22][23][24][25][26][27]. Part of the challenge with obtaining high-quality SnO is stabilizing Sn 2+ over Sn 4+ [28,29]. Indeed, thermodynamic phase diagrams omit SnO considering it metastable and to disproportionate to Sn and SnO 2 [30].…”
Section: Introductionmentioning
confidence: 99%
“…Recent theoretical studies, for example, have suggested that the excellent ferroelectric properties in Pb 2+ lead-based ferroelectrics might be alternatively obtained by stabilizing Sn as Sn 2+ in a perovskite [1]. Towards this end, heavily alloyed Sn:SrTiO 3 thin films were recently synthesized, and exhibited signatures of relaxor ferroelectricity in second harmonic generation experiments [2]. Relaxor-like ferroelectricity is usually thought to result from the formation of the polar nano-regions coupled to other changes in the crystal lattice, which are readily measureable with high-angle annular dark-field scanning transmission electron microscopy (HAADF STEM) [3].…”
mentioning
confidence: 99%
“…O método de reações de estado sólido foi o mais utilizado para a obtenção das composições em forma de pó e cerâmicas policristalinas, abrangendo também os métodos de tape-casting, dos precursores poliméricos e de sol-gel. [38][39][40]42,43,[45][46][47][48][49][50] Em relação à preparação destes compostos na forma de filmes finos, amostras foram obtidas através de deposição por laser pulsado (Pulsed Laser Deposition -PLD), por solução química (Chemical Solution Deposition -CSD) e epitaxia de feixe molecular híbrido de baixa energia (Molecular Beam Epitaxy -MBE). 38,40,42 Suzuki et al 46,47 prepararam amostras em que o estanho foi adicionado simultaneamente em sítios do estrôncio e do titânio dentro do intervalo de 0 < x < 0,1 para composições Sr1-aSnaTi1-bSnbO3 (SSTS) onde x = a+b.…”
Section: O Composto óXido De Estanhounclassified
“…Amostras do sistema SrTi1-xSnxO3 (STSO), com x = 0; 0,20; 0,40; 0,60; 0,80; 0,85; 0,90; 0,95 e 1,0 foram escolhidas com base nos estudos reportados na literatura. [38][39][40]42,43,[45][46][47][48][49][50] A escolha das temperaturas de tratamentos térmicos foi baseada em resultados reportados na literatura. 38,45,48 As condições de tratamentos térmicos foram realizadas em atmosfera ambiente e as taxas de aquecimento e de resfriamento usadas foram ambas de 10 °C/min.…”
Section: Composição Das Amostrasunclassified
See 1 more Smart Citation